Pengaruh Kualitas Informasi Dan Kepercayaan Konsumen Terhadap Minat Beli Produk Fashion Secara Online Melalui Facebook - Andria Firdausan; Yeye Suhaety; Syafruddin (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
This study was conducted to examine the extent to which information quality and consumer trust influence the interest in purchasing fashion products online through the Facebook platform. The study population included all active Facebook users in Indonesia who had purchased fashion products, either through the Marketplace feature or buy and sell groups. The research sample was selected using purposive sampling, and 100 respondents were successfully collected. Primary data was obtained through an online questionnaire distributed using Google Forms. The research instrument used a five-point Likert scale, where respondents were asked to provide their level of agreement with statements related to information quality, trust, and purchasing interest. Data analysis used the Partial Least Square – Structural Equation Modeling (PLS-SEM) approach, which was run using SmartPLS version 4.0 software. This method was chosen because it is capable of testing the relationship between latent variables comprehensively, even though the research sample size was not very large. The results of the analysis showed that information quality did not have a significant effect on consumer interest in purchasing fashion products through Facebook. Conversely, consumer trust was found to have a positive and significant effect on purchase interest. These findings confirm that in the context of online transactions on social media, trust in the seller and the reliability of the platform are more decisive factors than the quality of information.